Study of the structural and optical propertiesof ZnO and ZnO/Fe2O3 thin films grown by chemical bath deposition . - Qasim Chfat Abdulridha; Hussein Ali Noor (Al-Qadisiyah Journal of Pure Science, 2020)
ZnO andZnO/Fe2O3 composite thin films were prepared by chemical bath deposition technique with thicknesses (150±20) nm. X–ray diffraction analysis showed that pure and composite films polycrystalline in nature with Hexagonal structure and the preferred orientation  along (100 ) plane. The calculated crystallite size of the deposited films are found to be decreases with  composite films .Thesurface morphologyof the films was studied by Atomic force  microscope ,the surface morphology of pure and ZnO composite films are homogeneous distribution. The optical properties of all deposited ZnO and composite films contained study of transmittance and absorbance spectral in the range of wave length (300- 1100)nm, Transmittance increased with composite films, The value of the optical energy gap (Eg) were found decrease with composite films due to the effective electron/holes at the inter faces of ZnO/Fe2O3.